Analysis of Gait Pattern Affected by Various Disease : A Review (International Journal of Scientific Research in Science and Technology, 2024)
Gait is pattern of walking of individual, is unique pattern of a person. The gait pattern is affected by various disease, ill condition of a person. In this review article we discuss about various diseases by which gait of an individual gets affected. Some disease are ; Parkinson’s disease (PD) is a degenerative brain disorder causing shuffled gait, impaired balance, and freezing of gait. Morquio A syndrome, a group of disorders called mucopolysaccharidosis, can lead to vision, hearing, bone, brain, and heart problems. The anterior cruciate ligament (ACL) is a key stabilizer in the knee, and a torn ACL can cause instability when walking or changing directions. Examination of the gait pattern of a those person who having a disease such as ; Parkinson’s disease, Morquio A syndrome, Anterior Crucial Ligament, etc. In normal human the Gait Cycle has two phases ; Stance and swing phase. The stance phase covers approx 60% gait cycle and swing phase covers remaining 40% of gait cycle. In further studies we can analysis on how this cycle varies in abnormal walking.These review article summarises about gait pattern affected by various diseases. Study of gait pattern used for solving criminal cases as we can recognize various abnormalities a person may have by the analysis of his or her gait pattern. It is used as secondary evidence. By using gait pattern we can find out individuals age, sex, and height.